2014
DOI: 10.2174/1871520614666140608150448
|View full text |Cite
|
Sign up to set email alerts
|

Deoxypodophyllotoxin Isolated from Juniperus communis Induces Apoptosis in Breast Cancer Cells

Abstract: The study of anticancer properties from natural products has regained popularity as natural molecules provide a high diversity of chemical structures with specific biological and medicinal activity. Based on a documented library of the most common medicinal plants used by the indigenous people of North America, we screened and isolated compounds with anti-breast cancer properties from Juniperus communis (common Juniper). Using bioassay-guided fractionation of a crude plant extract, we identified the diterpene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 0 publications
2
31
0
Order By: Relevance
“…In the present study, DPPT significantly inhibited cell proliferation and cell apoptosis of DU-145 cells in a dose-and time-dependent manner. Several studies indicated that DPPT significantly induced cell apoptosis of HeLa cells (14), breast cancer cells (15) and non-small cell lung cancer cells (16). These results indicated that DPPT may be considered as a drug to target PCa.…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, DPPT significantly inhibited cell proliferation and cell apoptosis of DU-145 cells in a dose-and time-dependent manner. Several studies indicated that DPPT significantly induced cell apoptosis of HeLa cells (14), breast cancer cells (15) and non-small cell lung cancer cells (16). These results indicated that DPPT may be considered as a drug to target PCa.…”
Section: Discussionmentioning
confidence: 93%
“…Although DPT induced apoptosis of the human BC mDA-MB-231 cell line in vitro (Benzina et al, 2015), little research has been conducted on the efficacy of DPT on the MCF-7 cell line.…”
Section: Discussionmentioning
confidence: 99%
“…A physiologically based pharmacokinetics model was also established for better efficacy and safety assessment (Chen et al, 2016). Previous studies have demonstrated that DPT exerts an anti-tumor effect on the human BC MDA-MB-231 cell line in vivo and in vitro (Benzina et al, 2015;Khaled et al, 2016). However, the effect of DPT on drug-resistant cancer cells has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…ERK and NFκB signaling pathways within hours of treatment[324]. Antitumor effect of DPT on MDA-MB-231 human breast cancer xenografts in vivo[325] and in vitro[326].…”
mentioning
confidence: 99%